Elasticity of demand of an antidepressant drug in Colombia as an strategy to assess market power (2016)
This article develops an estimation of the price elasticity of demand of a medication 'type' for treating depression. This disorder affects physically and mentally a big part of the population around the world. This disorder is considered an important public health problem whose preva-lence has been increasing. For the purpose of this research two econometric models of vectors were estimated for the previous period of the issuance of Circular 03 of 2013, which regulates the price of medications in Colombia. The outcomes of the estimation show a non-significant price elasticity of 0.35 %, that is to say, changes in price do not generate the expected response in demand. This result suggests that the company, which produces this type of medication, exerts significant power in the market. Therefore, this result proves the need to implement the Circular.